1996
DOI: 10.1002/pro.5560050812
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the tyrosines to the structure and function of the human U1A N‐terminal RNA binding domain

Abstract: RNA binding domains (RBDs) are members of a large family of proteins that share minimal sequence conservation but adopt an a0 sandwich global fold. Defining the contributions of specific amino acids to RBD structure and RNA binding is critical to understanding the functions of these proteins. In these experiments with the human UlA N-terminal RNA binding domain (RBDl), the contributions from each of its four tyrosines to protein structure, stability, and RNA binding were measured. Each tyrosine was substituted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 52 publications
4
21
0
Order By: Relevance
“…Charged residue substitutions at these sites were always found to inactivate the protein. Six additional examples of effects of Asp substitutions of buried, noncharged residues were obtained from the Protherm database (http:͞͞gibk26.bse.kyutech.ac.jp͞jouhou͞ protherm͞protherm search.html): A52D and I53D in RNaseH (36,37), L133D in case of T4 lysozyme (38), S91D in hen egg white lysozyme (39), Y282D in case of Lac repressor (40), and Y78D in U1A protein (41). In all of the cases, there was a drastic decrease in protein thermodynamic stability relative to WT.…”
Section: Analysis Of Previous Mutational Studiesmentioning
confidence: 99%
“…Charged residue substitutions at these sites were always found to inactivate the protein. Six additional examples of effects of Asp substitutions of buried, noncharged residues were obtained from the Protherm database (http:͞͞gibk26.bse.kyutech.ac.jp͞jouhou͞ protherm͞protherm search.html): A52D and I53D in RNaseH (36,37), L133D in case of T4 lysozyme (38), S91D in hen egg white lysozyme (39), Y282D in case of Lac repressor (40), and Y78D in U1A protein (41). In all of the cases, there was a drastic decrease in protein thermodynamic stability relative to WT.…”
Section: Analysis Of Previous Mutational Studiesmentioning
confidence: 99%
“…Many structural, biochemical, and mechanistic studies have focused on defining the aspects of U1A and U1hpII that are important for their very high affinity interaction (Scherly et al 1989(Scherly et al , 1990LutzFreyermuth et al 1990;Hall and Stump 1992;Hall 1994;Oubridge et al 1994;Kranz et al 1996;Zeng and Hall 1997;Hall 1998, 1999;Katsamba et al 2001Katsamba et al , 2002a. In 1 vitro selection (SELEX) experiments demonstrated that U1A displays high specificity for a 7-nucleotide (nt) recognition sequence, AUUGCAC (Tsai et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The aspartic residue links the protein-RNA interface with the C-terminal domain. The C-terminal tail has been the subject of several studies, indicating its importance for RNA binding stability and specificity (12,14,18,22,(25)(26)(27). With a systematic truncation of the C-terminal tail, Hall (22) demonstrated a loss of 2 kcal͞mol of binding free energy when terminating the Cterminal at the position 95.…”
mentioning
confidence: 99%